Three new species of soldier beetles from Baltic amber (Coleoptera, Cantharidae) - Fanti, Fabrizio; Pankowski, Mary K. (Zootaxa, 2018)
Three new species of soldier beetles (Cantharidae) are described from late Eocene Baltic amber from the Kaliningrad Region of Russia on the coast of the Baltic Sea, i.e., Rhagonycha maryae sp. nov., Sucinorhagonycha samsockorum sp. nov. and Malthodes josephi sp. nov. Sucinorhagonycha samsockorum has a few antennomeres that are slightly dentate, making the new species appear intermediate between genus Sucinorhagonycha Kuśka, 1996, with filiform antennae, and genus Cacomorphocerus Schaufuss, 1892, which has saucer-shaped central antennomeres. This suggests that the relationship between the two genera may be closer than previously believed. Malthodes josephi is noteworthy because it has cuticular vesicles extruding from its abdominal segments that suggest their use for chemical defense. It is the first time that these vesicles have been discovered in Eocene species of soldier beetles. It is also the first time they have been seen in all extinct and extant species of the subfamily Malthininae and its genus Malthodes Kiesenwetter, 1852.